The effectiveness of group cognitive - behavioral therapy on emotional self - awareness and problem - solving skill of students with internet addiction - Fatemeh Kafi Nia; hadi farhadi (مجله علوم روانشناختی, 2020)
Background: Internet addiction is a phenomenon which damages the students’ social, communicative, cognitive, psychological and emotional processes of the students.  This study seeks to investigate whether cognitive-behavioral group therapy will improve emotional self-awareness and problem solving ability of students with internet addiction in secondary school. Aims: The present study was conducted with the aim of investigating the effectiveness of group cognitive-behavioral therapy on emotional self-awareness and problem-solving skill of secondary high school students with internet addiction. Method: The research method was quasi-experimental with pretest, posttest, control group and 45-day follow-up. The statistical population included all secondary high school students with internet addiction who were 40 students owning the criteria of entering the study and were purposefully selected and randomly replaced into experimental and control groups. The applied instruments in the study included internet addiction questionnaire (Yang, 1996), emotional self-awareness questionnaire (Grant, et.al, 2002) and problem-solving questionnaire (Hepner, 1988). The experimental group received group cognitive-behavioral therapeutic intervention in nine ninety-minute sessions during two-and-a-half months once a week while the control group didn’t receive them. Then the students in both groups took the posttest. The follow-up stage was administered after 45 days. The data analysis of the study was done mixed ANOVA method. Results: The results showed that group cognitive-behavioral therapy has significant effect on emotional self-awareness and problem-solving skill of the students with internet addiction at the posttest and follow-up stages (p<0/001). Conclusions: According to the findings of the present study it seems that through cognitive-behavioral therapy, emotional self-awareness and problem-solving skill of the students with internet addiction can be increased.